Random monoallelic expression of genes on autosomes: Parallels with X-chromosome inactivation. (August 2016) - Gendrel, Anne-Valerie; Marion-Poll, Lucile; Katoh, Kimiko; Heard, Edith
Abstract: Genes are generally expressed from their two alleles, except in some particular cases such as random inactivation of one of the two X chromosomes in female mammals or imprinted genes which are expressed only from the maternal or the paternal allele. A lesser-known phenomenon is random monoallelic expression (RME) of autosomal genes, where genes can be stably expressed in a monoallelic manner, from either one of the parental alleles. Studies on autosomal RME face several challenges. First, RME that is based on epigenetic mechanisms has to be distinguished from biased expression of one allele caused by a DNA sequence polymorphism in a regulatory element. Second, RME should not be confused with transient monoallelic expression often observed in single cell analyses, and that often corresponds to dynamic bursting of expression. Thanks to analyses on clonal cell populations, the existence of RME in cultured cells is now well established. Future studies of RME in vivo will have to overcome tissue heterogeneity and certain technical limitations. Here, we discuss current knowledge on autosomal RME, as well as possible mechanisms controlling these expression patterns and potential implications for development and disease, drawing parallels with what is known for X-chromosome inactivation, a paradigm of random monoallelic expression.